Efektivitas Program Pendidikan Lanjut Usia Terhadap Kualitas Hidup Lansia di Komunitas : A LITERATUR REVIEW - Ainun Jariah; Kusbaryanto Kusbaryanto (Jurnal Keperawatan Muhammadiyah, 2019)
Background: The elderly education program is a long-term learning model aimed at the elderly to improve their knowledge, especially regarding health. Education and learning are considered to be important factors in facilitating participation in society and enabling older people to enjoy positive quality of life as they age. By actively participating in this activity can improve the quality of life in the elderly. Objective: To determine the effectiveness of the elderly education program on improving the quality of life in the elderly. Method: The method of writing this study with a literature review and using the Google Scholar, Pubmed, Science Direct database, using Keywords: "Community-based intervention, Lifelong learning, Eduction, Quality of life, Elderly". Results: From 7 journals obtained, 1 study was conducted on postmenopausal women, 5 studies on male and female respondents and 1 study did not detect the sex of respondents. Revealed the results that the elderly education program was effective to improve the quality of life of the elderly after several types of peer education programs, lively later life, social activities, counseling groups, pro balance programs, health welfare education, and healthy lifestyle education were carried out. Conclusion: This review of the literature review found results that were effective in several types of education programs. The elderly education program is one of the effective programs to improve the quality of life in the elderly.